Synthesis, Characterization and Cardioprotective Activity of Some Novel Benzotriazole and Pyrazole Derivatives - Gudaparthi, Vijayalakshmi; Bharathi, K.; Panda, Jagadeesh (Asian Journal of Chemistry, 2010)
A series of N-(1-(1H-benzo[d]) [1,2,3]triazol-1-yl)-2,2-dimethyl propyl)-2-(substituted phenyl) acetamide derivatives and methyl 5-((4-(2,5-disubstituted phenyl) furan-2 carboxylate derivatives are prepared from different substituted aryl carboxylic acids, phenyl acetic acid and cinnamic acid, respectively. All the synthesized compounds are investigated for cardioprotective activity by ischemia reperfusion method, while all the compounds show significant activity.